Highly stereoselective and enantiodivergent synthesis of cyclopropylphosphonates with engineered carbene transferases. Issue 29 (6th June 2022) - Ren, Xinkun; Chandgude, Ajay L.; Carminati, Daniela M.; Shen, Zhuofan; Khare, Sagar D.; Fasan, Rudi
Abstract : Two enantiocomplementary myoglobin-based carbene transfer biocatalysts were developed for the synthesis of cyclopropylphosphonate esters with high diastereo- and enantioselectivity and in high yields. Abstract : Organophosphonate compounds have represented a rich source of biologically active compounds, including enzyme inhibitors, antibiotics, and antimalarial agents. Here, we report the development of a highly stereoselective strategy for olefin cyclopropanation in the presence of a phosphonyl diazo reagent as carbene precursor. In combination with a 'substrate walking' protein engineering strategy, two sets of efficient and enantiodivergent myoglobin-based biocatalysts were developed for the synthesis of both (1 R, 2 S ) and (1 S, 2 R ) enantiomeric forms of the desired cyclopropylphosphonate ester products. This methodology enables the efficient transformation of a broad range of vinylarene substrates at a preparative scale ( i.e. gram scale) with up to 99% de and ee. Mechanistic studies provide insights into factors that contribute to make this reaction inherently more challenging than hemoprotein-catalyzed olefin cyclopropanation with ethyl diazoacetate investigated previously. This work expands the range of synthetically useful, enzyme-catalyzed transformations and paves the way to the development of metalloprotein catalysts for abiological carbene transfer reactions involving non-canonical carbene donor reagents.